Determinants of Pneumonia Symptoms in Toddlers in the Paal V Health Center Working Area of Jambi City - Mellina mellina Manurung; Fitria Eka Putri; Adelina Fitri; Rumita Ena Sari; Andree Aulia Rahmat (Universitas Malahayati Lampung, 2024)
ABSTRACT Pneumonia is a disease in children under five which causes the highest number of deaths at the global level. Pneumonia cases in toddlers continue to increase and Indonesia is ranked 8th in the world. The aim of this research is to determine the factors associated with pneumonia symptoms in toddlers in the working area of the Paal V Health Center, Jambi City. Cross sectional research design. The research was conducted in the Paal V Community Health Center Working Area, Jambi City. The total sample was 70 toddlers taken using Accidental Sampling. The independent variables are house temperature, house humidity, residential density, house ventilation, lighting, smoking habits, mother's knowledge and exclusive breastfeeding. Data were analyzed using the Chi Squar e or Fisher Exact test. Toddlers with Pneumonia Symptoms are 65.7%. Factors associated with pneumonia symptoms in toddlers are house humidity (PR=0.60; 95% CI=0.37-0.95), house lighting (PR=0.55; 95% CI=0.29-1, 04), smoking habits (PR=1.50; 95% CI=098-2.28) and maternal knowledge (PR=2.46; 95% CI=1.08-1.97). Meanwhile, those that are not related to pneumonia symptoms in toddlers are house temperature, house ventilation, residential density and exclusive breastfeeding. Risk factors for pneumonia symptoms in toddlers are house humidity that does not meet the requirements, house lighting that does not meet the requirements, the presence of smoking habits in the house, poor maternal knowledge. It is hoped that mothers who have toddlers will pay attention to the physical environment of the house and reduce smoking habits in the house Keywords: Pneumonia, Environment, Child, Mother